2023
DOI: 10.1093/noajnl/vdad083
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating hematologic parameters in newly diagnosed and recurrent glioblastoma: Prognostic utility and clinical trial implications of myelosuppression

Abstract: Background Glioblastoma patients are treated with radiation therapy, chemotherapy, and corticosteroids, which can cause myelosuppression. To understand the relative prognostic utility of blood-based biomarkers in GBM and its implications for clinical trial design, we examined the incidence, predictors, and prognostic value of lymphopenia, neutrophil-to-lymphocyte ratio (NLR) and platelet count during chemoradiation (CRT) and recurrence. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Similarly, Le Rhun et al. ( 29 ) reported that grade 3/4 lymphopenia during concomitant radiochemotherapy but not during maintenance temozolomide chemotherapy was significantly associated with inferior overall survival in univariate and multivariate analysis. Deng et al.…”
Section: Standard Therapy-related Immunosuppression In Glioblastomamentioning
confidence: 89%
See 2 more Smart Citations
“…Similarly, Le Rhun et al. ( 29 ) reported that grade 3/4 lymphopenia during concomitant radiochemotherapy but not during maintenance temozolomide chemotherapy was significantly associated with inferior overall survival in univariate and multivariate analysis. Deng et al.…”
Section: Standard Therapy-related Immunosuppression In Glioblastomamentioning
confidence: 89%
“…Sex is another confounding factor of therapy-related lymphopenia. In two large cohort studies (n>700 and n>2000), women were found to be more likely to develop lymphopenia than men ( 29 , 58 ). Remarkably, 21-47% of patients with glioblastoma/gliomas treated with radiochemotherapy developed long-lasting grade 3/4 lymphopenia ( 29 , 47 52 , 58 60 ), although there were studies reporting a less frequent occurrence of grade 3/4 lymphopenia during or after standard therapy (2.9-10%) ( 53 , 61 , 62 ).…”
Section: Standard Therapy-related Immunosuppression In Glioblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…Deng et al. reported that 11.9% (out of n=469) of patients with glioblastoma (median age: 60.3; range: 19–94) had grade 3/4 lymphopenia (<500 cells/µl) preoperatively and 15.4% (out of n=628) postoperatively and before standard radiochemotherapy ( 48 ). In the elderly group (median age: 71 years), only 57% (out of n=72) of patients had normal baseline total lymphocyte counts ( 49 ).…”
Section: Glioma/glioblastoma-related Changes In Circulating Immune Cellsmentioning
confidence: 99%
“…However, the independent prognostic significance of NLR remains debatable ( 55 ). High NLR during standard therapy was also associated with worse overall survival regardless of steroid use in multivariate analysis ( 48 ), and a decline of NLR during or post-therapy was associated with longer overall survival of patients with glioblastoma in multivariate analyses in prospective ( 53 ) and retrospective studies ( 57 , 119 , 134 ). NLR was prognostic in patients with recurrent glioblastoma ( 119 , 135 ).…”
Section: A High Neutrophil-to-lymphocyte Ratio Is An Independent Prog...mentioning
confidence: 99%